Investigating gaydom turning points in Body 2 Body - Razali, Amirah; Noor, Rohimmi; Talif, Rosli (Universiti Putra Malaysia Press, 2015)
Numerous studies attempting to establish a genetic cause for homosexuality have been conducted since the early 1990s that have not been proven to be either valid or reliable. To date, the quest to establish the existence of a single chromosome in humans that would identify a person's homosexual identity seems futile as there are no scientific findings or DNA test results that have proven that such a third gender can be biologically determined. Therefore, on the premise that homosexuality, like race, is related to nurture rather than nature in the great nature versus nurture debate, this paper focuses on analysing the minds of lesbian, gay, bisexual and transsexual (LGBT) individuals by investigating the turning points to gaydom of several characters in selected short stories from the collection in Body 2 Body - A Malaysian Queer Anthology by examining their feelings and decisions when they decide to adopt LGBT identity. This paper also discusses the processes that are involved in the transformation of the characters' sexual identity. In addition, with Freudian psychic zones in mind, this paper also tries to determine whether these characters' id, as opposed to their ego and superego, take control of their desires, or whether the tendency towards homosexuality exists naturally within them and is the reason they choose to become and remain part of the LGBT community.